Persaingan Politik Dua Penguasa Besar Dunia Islam Abad 15 M: Sultan Bayazid dan Timur Lenk - Septian Fatianda (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
After the fall of the Abbasid dynasty in 1258 due to the attack of the Mongols, the mecca of great Islamic power began to move to the Ottoman Empire and the Timurid Empire. The two great powers were led by Sultan Bayazid and Timur Lenk, respectively. The development and power possessed by these two rulers brought them to the point where they competed with each other in spreading political influence. Policies to undermine each other's territory are inevitable. They finally met in the great war in 1402 in Ankara. The war was finally won by Timur Lenk's troops and Sultan Bayazid became a prisoner of war. The paper uses historical methods that focus on literature review to find sources and present research answers. This paper aims to describe the causes of political competition and its implications for the Islamic world at that time.